Green Coconut (Cocos nucifera L.) Husk Extract as Milk Freshness Indicator in Chitosan/ Polyvinyl Alcohol-based Smart Packaging Films - Barleany, Dhena Ria; Yulvianti, Meri; Jayanuddin, Jayanuddin; Rasyid Setiadi, Hilman; Mulyo Prasetyo, Rizky (Jurnal Riset Kimia, 2025)
The growing demand for sustainable and eco-friendly food packaging has prompted research into innovative solutions that tackle environmental challenges and consumer health concerns. Food spoilage typically results from microbial activity, which is subsequently influenced by alterations in pH levels within the packaging environment. Plants, such as green coconut husk extract, contain anthocyanin, a water-soluble natural pigment with significant antioxidant and antibacterial properties, whose color changes in response to variations in the surrounding pH. This research focuses on the development of a pH-responsive packaging film utilizing chitosan and polyvinyl alcohol (PVA), integrated with green coconut (Cocos nucifera L.) husk extract, through a casting method to monitor milk freshness. An extraction procedure employing a maceration technique was conducted on green coconut husk utilizing methanol solvent with the incorporation of 1 % HCl (v/v). The thickness, mechanical properties, and pH-responsiveness of the resulting films with varying extract to chitosan volume ratios were examined in detail. The films were subsequently employed to monitor real-time applications concerning milk freshness. The results indicated that the addition of green coconut husk extract resulted in significant variations in the thickness, tensile strength, and elongation at the break of the film samples. The films exhibited thicknesses between 0.28 and 0.38 mm, demonstrating optimal mechanical properties at an extract-to-chitosan ratio of 4:1 (v/v), with tensile strength (TS) and elongation at break (EB) recorded at 4.65 MPa and 3.625%, respectively. The films exhibited a pH-sensitive color change from dark red to brown in acidic conditions. The findings indicate that the PVA/chitosan smart film, which contains green coconut husk extract, has the potential to serve as a deterioration indicator in packaged milk products.